1993
DOI: 10.1207/s15328023top2002_3
|View full text |Cite
|
Sign up to set email alerts
|

Teaching Undergraduate Community Psychology: Integrating the Classroom and the Surrounding Community

Abstract: A n undergraduate course in community psychology is described. This course provides students with an integrative learning experience, combining academic coursework, exposure to current sociopolitical affairs, and personal experience in working with individuals living on the fnnges ofsociety. The course appears effective in introducing students to the content, methodology, values, and perspectives of this discipline. Factors thought to contribute to the success of the course are discussed.One can explain the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
5
0

Year Published

1994
1994
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 16 publications
1
5
0
Order By: Relevance
“…Finally, some students reported a change in future plans, as the project allowed them the opportunity to test their suitability for working with clinical populations. The students' experiences with the community project were similar to those reported previously (Chapdelaine & Chapman, 1999;Clements, 1995;Glenwick & Chabot, 1991;McCluskey-Fawcett & Green, 1992;Osborne & Gray, 1995;O'Sullivan, 1993). The community was equally enthusiastic about the students' efforts and abilities.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Finally, some students reported a change in future plans, as the project allowed them the opportunity to test their suitability for working with clinical populations. The students' experiences with the community project were similar to those reported previously (Chapdelaine & Chapman, 1999;Clements, 1995;Glenwick & Chabot, 1991;McCluskey-Fawcett & Green, 1992;Osborne & Gray, 1995;O'Sullivan, 1993). The community was equally enthusiastic about the students' efforts and abilities.…”
Section: Discussionsupporting
confidence: 74%
“…In the past, most instructors have focused on the benefits for the students participating in fieldwork. Such benefits include the opportunities for students to apply psychological theories to real-world problems, to test their suitability for careers working with special populations, and to explore the issues and obstacles that contemporary psychologists face (Clements, 1995;Glenwick & Chabot, 1991;McCluskey-Fawcett & Green, 1992;Osborne & Gray, 1995;O'Sullivan, 1993). Moreover, students involved in fieldwork experience combined with traditional classroom instruction express high levels of satisfaction with the course and a greater appreciation for the subject matter being studied as well as improved learning (Chapdelaine & Chapman, 1999;Clements, 1995;McCluskey-Fawcett & Green, 1992).…”
mentioning
confidence: 99%
“…Role-playing strategies, long considered essential for teaching empathy and perspective taking (Carkhuff, 1969;Rogers, 1957), represent another type of experiential activity used to facilitate understanding of various psychological concepts (e.g., Hess, 1976;Johnson & Corser, 1998;McCaughey, 1991;Rosnow, 1990;Sheldon, 1996). Furthermore, role plays appear to help dispel misperceptions about specific groups or cultures (O'Sullivan, 1993;Pulos, 1993). McGregor's (1993) meta-analysis found role plays effective in reducing student racial prejudice, whereas others indicated that role playing decreases undergraduates' negative stereotyping of people with psychological problems and increases empathy for future clients (Anderson, Gundersen, Banken, Halvorson, & Schmutte, 1989;Puente, 1990).…”
mentioning
confidence: 99%
“…Research review projects (e.g., term papers, literature reviews) were required of students in 83% of the courses, whereas only 42% of the courses included student service placements. This finding was particularly surprising because several writers (e.g., McLean, Johnson, & Eblen, 1977;O'Sullivan, 1993) have emphasized service and field work as an essential component of a community psychology course. The courses reviewed in our sample did not appear to place such an emphasis on field work.…”
Section: Research and Service Practicamentioning
confidence: 99%